PROMOTING LISTENING STRATEGIES AND GROUP WORK FOR TERTIARY STUDENTS LEARNING OF LISTENING COMPREHENSION - Bayu Hendro Wicaksono (University of Muhammadiyah Malang, 2015)
Indonesia university graduate level of English listening comprehension is usually lower than the other three skills of writing, reading and speaking (Prapphal, 2003), and the culprit related to this causally is inadequate classroom teaching (Foley, 2005, p. 233). Consequently, this research project investigates the implementation of an innovative teaching intervention in some Indonesia tertiary listening comprehension class. The main aims were to: 1. Examine the benefits of the teaching model 2. Explore individual student regulation of listening tasks 3. Examine influences of group interaction on learning in this context.Both the intervention and the research project are guided by a socio-cultural theory of second or foreign language (L2) acquisition which views human learning and development as dependent on a repeated interplay between social and individual processes (John-Steiner & Mahn, 1996, p. 191; Vygotsky, 1978; Lantolf & Thorne, 2006). The intervention will involve both individual and group work, combining a strategy-based listening instruction model based on the Cognitive Academic Language Learning Approach (CALLA) (Chamot et al., 1999) with a three-step task design. This model will provide students with strategy training and practice in selecting and using appropriate strategies in the meta-cognitive processes of planning, monitoring, problem-solving and evaluating. The research is designed to take place over two year, with 30 participants from each classes of 30, and generating both qualitative and quantitative data from numbers of tertiary classes, while prioritising the former. The qualitative data will be collected through video recordings of classroom activities, teacher-researcher's field notes, and group interviews at the end of the intervention. The quantitative data are generated through pre- and post-tests conducted with the participating students. Data sources and methods are triangulated for the data analysis, which was thematic in the first instance. Vygotskian activity theory explicated by Engeström (1987) will then be used in further interpretation. This theory offers an effective analytical framework accommodating the interconnections between individual and social processes involved in learning listening comprehension.